2021
DOI: 10.3390/biom11040542
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalimide-Containing BP100 Leads to Higher Model Membranes Interactions and Antimicrobial Activity

Abstract: In a large variety of organisms, antimicrobial peptides (AMPs) are primary defenses against pathogens. BP100 (KKLFKKILKYL-NH2), a short, synthetic, cationic AMP, is active against bacteria and displays low toxicity towards eukaryotic cells. BP100 acquires a α-helical conformation upon interaction with membranes and increases membrane permeability. Despite the volume of information available, the action mechanism of BP100, the selectivity of its biological effects, and possible applications are far from consens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
3
0
1
Order By: Relevance
“…These properties make this class of compounds, which are widely used as fluorescent markers in biology and medicine, important [9][10][11][12]. With success, 1,8-naphthalimide derivatives are used in the synthesis of compounds with biological activity [13][14][15]. Another cutting-edge field of application of this class of compounds is their use as a signaling fragment in the design of optical molecular devices with sensing properties [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…These properties make this class of compounds, which are widely used as fluorescent markers in biology and medicine, important [9][10][11][12]. With success, 1,8-naphthalimide derivatives are used in the synthesis of compounds with biological activity [13][14][15]. Another cutting-edge field of application of this class of compounds is their use as a signaling fragment in the design of optical molecular devices with sensing properties [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In this article, the authors investigated the permeabilising capacity of the peptide by changing the lipid composition of the liposomal bilayer by monitoring the fluorescence properties of naphthalimides. 19 Similarly, the fluorescence properties of naphthalimides have been explored to develop selfreporting vectors for nucleic acid delivery using a liposomal carrier. 20,21 To the best of our knowledge, only one article has been published studying the loading of a naphthalene-based diimide derivative (AN169) in liposomes avoiding the use of DMSO as a solubilising agent in in vitro and in vivo experiments.…”
Section: Introductionmentioning
confidence: 99%
“…This adaptability has led to extensive applications in several fields, ranging from selective ion probes and colorful dyes but also in the pharmacological field [12][13][14][15][16]. Several studies reported that compounds which contain a naphthalimide-core scaffold present increased bioactivity, allowing for its usage as an antitumor [17], antidepressant [18], antiviral [19], antiprotozoal [20], anti-inflammatory [21], anti-tuberculosis [22] and antibacterial agent [13]. This increased bioactivity is mainly due to its DNA-binding mechanisms, which are mostly derived from the tricyclic planar ring configuration of the naphthalimide scaffold [12].…”
Section: Introductionmentioning
confidence: 99%